Conflict of Interest: Legal and Ethical Aspects in Local Self-Government in Slovakia - Ondrej Mitaľ (Central European Public Administration Review)
Serving the public interest should be perceived as a fundamental goal of public administration. Regarding the complexity of social reality, various motives could influence public officials’ behaviour and decision-making. Conflict of interest is mostly discussed as an issue, which relates to activities of elected officials. In this sense, the paper concentrates on rules and standards connected with the conflict of interest, which have to be observed by the public officials. The paper tries to be an interdisciplinary insight and emphasizes the legal and ethical approaches to the examined issue. In this sense, the paper tries to examine the managing of risks and impacts of the examined issue at the local level of self-government in the Slovak Republic. The hypothesis is based on the precondition that ethical norms can define aspects of the conflict of interest more precisely than the relevant legal acts. In the paper, the methods of content analysis, abstraction, comparison and synthesis are involved. The benefit of paper is based on the finding that ethical norms could define important aspects of the conflict of interest more precisely than legal acts. The author presumes that complementarity of legal systems and ethical infrastructure could minimize contradictory and negative impacts of the conflict of interest. Based on this fact, local self-government units should adopt codes of ethics if they want to improve the managing of risks and impacts of the conflict of interest.